Konstruksi Politik Identitas Panggung Demokrasi Pemilihan Kepala Desa Kabupaten Mandailing Natal - Muhammad - Iqbal; Hasan Sazali; Mohd Rafiq (Ittishol: Jurnal Komunikasi dan Dakwah, 2023)
Elections for village heads are part of the implementation of a democratic system as a ground-level election that touches the community. As Indonesians, we both have the right to express opinions and we can choose anyone to be our leader. Everything is regulated in state regulations. When a candidate for village head is elected, this is done directly by the people included in the election data. It is undeniable that the election for village head candidates is often tinged with identity-political overtones. Such a policy was made so that the winning team could later win the political polemic. In fact, there were many incidents when political battles occurred in various places, one of which was in Mandailing Natal Regency. Not only identity politics, but also other identity politics such as ethnic, religious and cultural identity. This research uses a qualitative approach with descriptive methods. Then the sources and data collection techniques were carried out using interview techniques. In addition, this research was conducted with secondary data by reviewing literature from several journals and references from online media. The study concluded that part of identity politics in Mandailing Natal District is an emphasis on ethnic, cultural and religious identity. In fact, the presence of monetary/money policies was inevitable in the political upheaval that occurred in several villages in Mandailing Natal District.